2021
DOI: 10.1038/s41598-021-81471-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential key genes and pathways associated with the Pashmina fiber initiation using RNA-Seq and integrated bioinformatics analysis

Abstract: Pashmina goat (Capra hircus) is an economically important livestock species, which habitats the cold arid desert of the Ladakh region (India), and produces a princely animal fiber called Pashmina. The Pashmina goat has a double coat fleece as an adaptation to the very harsh cold winters the outer long coarse hair (guard hair) produced from primary hair follicles and the inner fine Pashmina fiber produced from secondary hair follicles. Pashmina fiber undergoes a circannual and synchronized growth cycle. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Most of these genes are related to cell growth, and some researchers have found that the treatment of acute wounds in rats with IGF1 -overexpressing fibroblasts can significantly improve the rate of wound healing ( 37 ). ITGAV has been proven to be a key gene for the initiation of goat cashmere growth ( 38 ). Cyclin-dependent kinase 6 ( CDK6 ) is an important regulator of the cell cycle and plays a role to similar CDK4 as a mediator of keratinocyte proliferation ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these genes are related to cell growth, and some researchers have found that the treatment of acute wounds in rats with IGF1 -overexpressing fibroblasts can significantly improve the rate of wound healing ( 37 ). ITGAV has been proven to be a key gene for the initiation of goat cashmere growth ( 38 ). Cyclin-dependent kinase 6 ( CDK6 ) is an important regulator of the cell cycle and plays a role to similar CDK4 as a mediator of keratinocyte proliferation ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hair growth has a complex mechanism regulated by a variety of endogenous and exogenous factors [ 28 ]. Understanding the genetic basis of wool phenotype assist in improving the efficiency of wool production, and in identifying the molecular determinants of wool density and phenotype differences.…”
Section: Discussionmentioning
confidence: 99%
“…KEGG database [ 58 ] was used for the identification of pathways regulated by gene-set. To gain insight into the functional and enrichment analysis g: profiler webserver was used [ 59 ] using Capra hircus as reference.…”
Section: Methodsmentioning
confidence: 99%